No money left for climate protection? - Menusch Khadjavi; Sonja Peterson; Sebastian Petrick; Wilfried Rickels (The crisis and beyond, 2009)
The ongoing global financial crisis has been preceded by a steady rise in global current account imbalances. Recently, in the course of the global recession, global imbalances have declined, albeit without having disappeared completely. As the outlook for global growth gets brighter, it is important to be aware of the possibility of again arising global imbalances in the future, since many of the structural reasons for the foregoing build up of imbalances remain largely in place. This is particularly important against the background of a close relationship between the global imbalances and the financial crisis. Important steps that would help to avoid the reoccurrence of unsustainable global imbalances and contribute to stabilize the global economy in the medium run are a tighter regulation of financial markets, the strengthening of the role of the IMF in monitoring global capital markets, and the development of social security systems and financial markets in emerging economies.
Keywords: 330; Konjunkturpolitik; Klimaschutz; Umweltschutzinvestition; Finanzmarktkrise; Welt